Anxiety levels in judokas participating in the 41th Inter-Army Military Championship of Judo 2017 - Ruiz-Barquín, Roberto; Robles Pérez, Juan José; García Estebaranz, Santiago (Revista de Artes Marciales Asiáticas, 2018)
The aims of this study were: to describe the anxiety levels of competitive judokas who participated in the 41st Inter-army Military Championship of Judo, year 2017; to detect differences in anxiety levels depending on sex and weight categories; to explore if there was a relation between the anxiety levels and the judokas’ final results at the tournament. The sample was composed of 28 judokas (18 men and 10 women) belonging to two teams (Army and Guardia Civil), having an average age of 34.29 years (SD = 5.12). Before competition, the ISRA-B questionnaire, answers version, was administered. The results showed that judokas had lower levels of cognitive anxiety (p<.05), physiological anxiety (p<.001) and motor anxiety (p<.001) than other samples of athletes. Likewise, there were significant differences in anxiety levels according to sex, having women higher levels of motor anxiety in (p<.05). In terms of weight, only significant results were found in male judokas (p<.05), where the heavier judokas had higher levels of cognitive anxiety (p<.05). Only significant correlations were found between motor anxiety levels and the position obtained in competition in the male group (rho = -.635, p<.05). The results confirmed the necessity to perform differential psychological interventions considering the sex and weight category variables.